MANAJEMEN PENINGKATAN MUTU SD NEGERI 1 GUMELAR SEBAGAI SEKOLAH UNGGULAN DI KECAMATAN GUMELAR KABUPATEN BANYUMAS - Kurniawan, Yusep; Andriani, Ana; Taniredja, Tukiran (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2020)
This research aims to: 1) find out how the management of improving the quality of SD Negeri 1 Gumelar as a superior school; 2) find out the impact of school quality improvement management on student achievement; 3) find out the impact of school quality improvement management on the results of USBN grade VI students. Research activities carried out at SD 1 Gumelar Elementary School. The study was conducted for 4 (four) months, starting from March until June 2019. This research is a descriptive study with qualitative and quantitative approaches. Data collection techniques and tools were carried out by distributing questionnaires and interviews. Data analysis was carried out qualitatively and quantitatively. The results of the study show that: 1) Gumelar Elementary School 1 has implemented management of quality improvement in eight national education standards well and optimally. Management of quality improvement that has not been optimal can be seen in graduate competency standards, educator standards and education staff as well as standards of facilities and infrastructure. 2) The management of quality improvement carried out has a very good impact on student achievement. It was proven that SD Negeri 1 Gumelar became the overall champion in the race activities at the sub district level in 2019. 3) The results of the study showed that the management of quality improvement had no impact on the results of USBN for Grade VI students in 2018 and 2019. The results of USBN in 2019 only reached 25 Gumelar District.